2012
DOI: 10.2320/matertrans.m2011272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electric Current on Microstructural Evolution in a Cold-Rolled 3% Si Steel

Abstract: The effect of electric current pulse (ECP) treatment on grain orientation in a cold-rolled Fe3%Si steel was investigated in this study. Results showed that the recrystallized nuclei preferred to form along the current direction in the primary period of recrystallization. The theoretical analysis revealed that the anisotropic nucleation orientation was ascribed to the different dislocation mobility derived from the electron wind force during the passing of electric current. Hence, the ECP treatment should be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…For Fe-3wt% Si alloys, electropulse has been found to promote the Goss-texture development during recrystallization [11,23]. Theoretically, electropulse is found affecting the kinetic barrier and free energy sequence of phases.…”
mentioning
confidence: 97%
“…For Fe-3wt% Si alloys, electropulse has been found to promote the Goss-texture development during recrystallization [11,23]. Theoretically, electropulse is found affecting the kinetic barrier and free energy sequence of phases.…”
mentioning
confidence: 97%
“…The possibilities for enhancing the diffusion by pulsed electric currents include an increase in the diffusion pre-exponential factor and/or a reduction in the diffusion activation energy [9]. Previously it has been reported that elongated SnPb eutectic grains and growth of lamellae occurred along the electrode directions [10] and that recrystallized nuclei in a cold-rolled silicon steel preferred to form along the current direction [11]. Furthermore, electric-current-induced oriented nanotwins formation with low electrical resistivity in Cu-Zn alloy [6] also suggests that the orientation of impurities may be affected by the application of electric current.…”
Section: Introductionmentioning
confidence: 99%
“…Because the effect of current on grain growth after nucleation is almost the same for the four groups, the different activation energy after ECP treatment can be trace back to the different distribution of grain boundary for samples before ECP treatment. Since the ECP treatment could increase nucleation rate of the high conductivity phase by the decrease of thermodynamic barrier during phase transformation, 7) it can be assumed that the grain boundary resistivity would be decreased with the increasing of angle between CD and RD.…”
Section: Resultsmentioning
confidence: 99%
“…4,5) Dai reported that the oriented nanotwins and segregation of lead were observed in ECP treated CuZn alloy. 6,7) Furthermore, Zhou found that the application of ECP could dramatically enhance the diffusion coefficient of a CuZn alloy. 8) However, the effects of current direction (CD) and the grain boundary resistivity on diffusion phase transformation induced by ECP have seldom been investigated.…”
Section: Introductionmentioning
confidence: 99%